Acceptance and Levels of Iron Gyoyam (Spinach Gyoza) as an Alternative Snack to Prevent Anemia in Young Women - Mochammad Wildzan Yuda Pratama; Juliana Christiyaningsih; Annas Buanasita; Nurul Hindaryani; Fahmi Hafid; Siti Zaharah Rosli (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Anemia is a condition in which blood hemoglobin levels are lower than normal in certain age and gender groups. Hemoglobin is the pigment in the blood that carries carbon dioxide and oxygen around the body. To confirm the results of a study on the acceptability and iron content of Gyo Yam (spinach dumplings) as an alternative snack to anticipate anemia in young women. Because this type of research aims to study the effect of one variable on other variables, or to test whether there is a change between one variable and another. This type of research is true experimental research. In this study, a laboratory test was conducted to test the formulation using the method used, namely ICP-OES (Inductively Coupled Plasma-Omission Spectroscopy) to measure iron levels. Result, each dumpling weighs 50 grams and contains 2.2 milligrams of iron.Conclusion, Gyoyam (Spinach Gyoza) Formula 3 can be used as an alternative snack to prevent anemia in young women.